Migraine and cardiovascular disease - Marcelo E. Bigal (Arquivos de Neuro-Psiquiatria)
Migraine, especially migraine with aura is an established risk factor for ischemic lesions of the brain. Recent evidence has also linked migraine with and without aura to a broader range of ischemic vascular disorders including angina, myocardial infarction, coronary revascularization, claudication and cardiovascular mortality. The topic is therefore of considerable interest. Accordingly, herein we review the association between migraine and cardiovascular disease. We start by briefly presenting diagnostic criteria for migraine and revising its pathophysiology. We follow by summarizing the evidence on the topic. We then briefly present the results of a recent meta-analysis. We close by highlighting results of a large epidemiological study conducted after the publication of the meta-analysis.